Acceptance of M-Pesa Service and its Effect on Performance of Small and Micro-Businesses in Kenya - Kalei, Ann; Wambugu, Hannah Wanjiku; Muturi, Peter Githae (International Journal of Managerial Studies and Research (IJMSR), 2016)
A lot of research has been done on the effect of mobile money on efficiency of and outreach of micro-finance loans in developing countries. Yet to date, there has been no quantitative test to show the factors driving the acceptance of mobile- money service, and whether the level of acceptance has any significant effect on the performance of small and micro-businesses in Kenya. This study investigated factors determining the acceptance of M-PESA service and the effect of M-pesa Service on small and micro-businesses in Kenya. It further investigated the challenges facing M-PESA users in Kenya. The study adopted a survey and case study design on a sample of 1230 small and micro-business operators in Limuru town in Kenya. ANOVA tests was used to show whether there are differences in average acceptance of the M-PESA service among consumers who had different views regarding: perceived ease of use, social influence, facilitating conditions and trust i.e security of the service. Regression analysis was used to show the actual effect of the acceptance of M-Pesa on small and micro-business performance. Results indicated that, there is a significant difference in acceptance of M-pesa by traders who had: reported different perceived ease of use, social influence, facilitating conditions by the provider and security of the system when transferring money. After controlling for the factors that influences performance, regression results indicated that, acceptance of M-pesa had positive and significant effect on the performance. Security of money transactions, sending money to the wrong persons and lack of electronic money float were identified as challenges facing M-PESA service users and agents in Kenya. The knowledge generated in this study is important to the business community in Kenya and Mobile money service providers in Kenya. A conclusion can be reached that M-Pesa is an intervention in business world that has contributed to improvement in performance of small and micro-business in Kenya. The recommendation is that micro- businesses should embrace mobile banking, for it is an intervention that will go a long way in improving lives for Kenyans.
Keywords: M-banking; M-PESA; M-PESA acceptance; Perceived ease of use; Social influence; Facilitating conditions and security of the system